Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1021/bi00212a006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the activity of protein tyrosine phosphatase 1C by its SH2 domains

Abstract: Full-length protein tyrosine phosphatase 1C (PTP1C), the catalytic domain of PTP1C (delta PTP1C), and the N-terminal SH2 domain truncated PTP1C (delta NPTP1C) were overexpressed in Escherichia coli and purified to near homogeneity. Various phosphorylated states of the synthetic phosphotyrosyl peptide TRDIYETDYYRK (IRP), corresponding to the major insulin receptor autophosphorylation sites, were used as substrates for the PTPs. There was no indication for selective dephosphorylation of any of the three phosphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 22 publications
(31 reference statements)
5
46
0
Order By: Relevance
“…Cbl is a substrate of SHP-1 (18), and SHP-1 activity is regulated by allosteric mechanisms involving interaction of its Src homology 2 domain with other proteins (19,20). We wondered whether dephosphorylation of Cbl after EphB6 cross-linking was related to changes in the interaction between Cbl and SHP-1.…”
Section: Interaction Between Ephb6 and Cblmentioning
confidence: 99%
“…Cbl is a substrate of SHP-1 (18), and SHP-1 activity is regulated by allosteric mechanisms involving interaction of its Src homology 2 domain with other proteins (19,20). We wondered whether dephosphorylation of Cbl after EphB6 cross-linking was related to changes in the interaction between Cbl and SHP-1.…”
Section: Interaction Between Ephb6 and Cblmentioning
confidence: 99%
“…24,25 SHP1 has been shown to silence the JAK/STAT pathway by dephosphorylating and inactivating JAK. [26][27][28][29] SHP1 has been reported to have tumor suppressor function. 30 In a previous study, we demonstrated that loss of SHP1 expression related to gene methylation is found in ALK ĂŸ ALCL cell lines and is detectable in the majority of ALK ĂŸ ALCL tumors.…”
Section: Introductionmentioning
confidence: 99%
“…SHP-1 is composed of a central catalytic domain, two SH2 domains at its N terminus, and a C terminus with potential tyrosine phosphorylation sites (23). The SH2 domains have been shown to be important for localization (24 -34) as well as for the regulation of SHP-1 catalytic activity (35,36). In vitro data suggest that the C terminus may also be involved in regulating the phosphatase activity of SHP-1 (reviewed in Ref.…”
mentioning
confidence: 99%